2014
DOI: 10.1093/jmcb/mju039
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl oxidase promotes bleomycin-induced lung fibrosis through modulating inflammation

Abstract: Enzymes involved in collagen biosynthesis, including lysyl oxidase (LOX), have been proposed as potential therapeutic targets for idiopathic pulmonary fibrosis. LOX expression is significantly upregulated in bleomycin (BLM)-induced lung fibrosis, and knockdown of LOX expression or inhibition of LOX activity alleviates the lung fibrosis. Unexpectedly, treatment of the mice with LOX inhibitor at the inflammatory stage, but not the fibrogenic stage, efficiently reduces collagen deposition and normalizes lung arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…A recent study in muscular fiber development identified LOXL3 as an enhancer and key regulator of integrin signaling, supporting the role of LOXL3 in pro-fibrotic signaling pathways 34 . Moreover, LOX inhibition was shown to be efficacious in early inflammatory phases of the Bleomycin-induced fibrosis model, suggesting that a LOX inhibitory component in an anti-fibrotic treatment approach could be beneficial 35 . Therefore, a detailed evaluation of the potential of dual LOX/LOXL2 or LOXL2/LOXL3 targeting should be conducted in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in muscular fiber development identified LOXL3 as an enhancer and key regulator of integrin signaling, supporting the role of LOXL3 in pro-fibrotic signaling pathways 34 . Moreover, LOX inhibition was shown to be efficacious in early inflammatory phases of the Bleomycin-induced fibrosis model, suggesting that a LOX inhibitory component in an anti-fibrotic treatment approach could be beneficial 35 . Therefore, a detailed evaluation of the potential of dual LOX/LOXL2 or LOXL2/LOXL3 targeting should be conducted in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…38 Notably, previous studies have uncovered that LOX expression is significantly elevated in bleomycin-induced pulmonary fibrosis and inhibition of LOX activity alleviates the pulmonary fibrosis. 39,40 However, the involvement of LOX in bleomycin-based sclerotherapy is undetermined. Herein, we observed that bleomycin not only markedly upregulated the expression and activity of LOX, but increased the mRNA expression of multiple ECM components in HUVEC, which was reversed by LOX suppression with BAPN.…”
Section: Discussionmentioning
confidence: 99%
“…B, Cell apoptosis was performed by flow cytometry analysis, and representative plots were shown. 37 Additionally, TGF-β 1 increases LOX expression and activity in vascular smooth muscle cell, which is critical in vascular remodelling. Values shown are mean ± SD from at least three independent experiments.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Inhibition of LOX impairs TGF-β 1 signalling and myofibroblast accumulation in bleomycin-induced lung fibrosis. 37 Additionally, TGF-β 1 increases LOX expression and activity in vascular smooth muscle cell, which is critical in vascular remodelling. 38 In the present study, we showed that siRNA TGF-β 1 could completely abolish the expression of LOX and inhibit hypoxia-induced PASMCs proliferation, suggesting that LOX may be a direct target of TGF-β 1 .…”
Section: Discussionmentioning
confidence: 99%